2023
DOI: 10.7454/ihpa.v8i1.6570
|View full text |Cite
|
Sign up to set email alerts
|

Potrait of Public Private Partnership Policy Substances in Regional Hospitals in Indonesia

Abstract: Public Private Partnership (PPP) is a strategy of the Indonesian Government to deal with budget constraints and overcome gaps in infrastructure, access, and quality of health services. PPP on the operational cooperation (KSO) model is the oldest and most widely applied practice by regional hospitals in Indonesia. The implementation of KSO must refer to government policies in the form of laws and regulations. Since its initial implementation until today, the Ministry of Home Affairs, as the body that oversees t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…For example, Wahyudi (2020) criticize the absence of minimum requirements for specialist doctors in the previous hospital classification regulation, which caused an uneven distribution of specialist doctors and affected the quality of healthcare services in Indonesia (Wahyudi et al, 2021). Additionally, research by Basabih (2023) reveals that an inadequate Public Private Partnership (PPP) framework can limit the autonomy of regional hospitals and hinder the improvement of healthcare services (Basabih, 2023). Martha (2020) also indicated that the effective occupational health and safety management system at Gadjah Mada University Hospital has not yet implemented an internal audit, which is a crucial element to ensure the consistent application of standards (Martha, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wahyudi (2020) criticize the absence of minimum requirements for specialist doctors in the previous hospital classification regulation, which caused an uneven distribution of specialist doctors and affected the quality of healthcare services in Indonesia (Wahyudi et al, 2021). Additionally, research by Basabih (2023) reveals that an inadequate Public Private Partnership (PPP) framework can limit the autonomy of regional hospitals and hinder the improvement of healthcare services (Basabih, 2023). Martha (2020) also indicated that the effective occupational health and safety management system at Gadjah Mada University Hospital has not yet implemented an internal audit, which is a crucial element to ensure the consistent application of standards (Martha, 2020).…”
Section: Introductionmentioning
confidence: 99%